PENGARUH OWNERSHIP STRUCTURE DAN FIRM SIZE TERHADAP CASH CONVERSION - Felicitas Fanny Gunawan; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aims to determine the direct influence of  Ownership Structure and Firm Size on Cash Conversion Cycle. The sample constituted of 128 manufacture companies listed in Indonesia Stock Exchange during the period of 2011-2016. The data were collected from annual reports, and then analyzed by using GRETL software.The finding revealed that there is negative  impact of Firm Size coefficient on Cash Conversion Cycle. However this study fails to find the impact of Ownership Structure on Cash Conversion Cycle